Research on the Dynamics Game Model in a Green Supply Chain: Government Subsidy Strategies under the Retailer’s Selling Effort Level - Xigang Yuan; Xiaoqing Zhang; Dalin Zhang (Complexity)
Based on dynamic game theory and the principal-agent theory, this paper examined different government subsidy strategies in green supply chain management. Assuming that the retailer’s level of selling effort involved asymmetric information, this study analyzed the impact of different government subsidy strategies on the wholesale price, the product greenness level, retail price, the level of selling effort, the manufacturer’s profit, and the retailer’s profit. The results showed that (1) the government’s subsidy strategy can effectively not only improve the product greenness level but also increase the profits of an enterprise in a green supply chain, which helps the retailer to enhance their selling effort; (2) regardless of whether the retailer’s level of selling effort was high or low, as the government’s subsidy coefficient increased, the wholesale price continued to decrease, and the product greenness level and retailer’s selling effort level also increased.